2014
DOI: 10.1007/s12010-014-1404-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus crustorum KH: Novel Prospective Probiotic Strain Isolated from Iranian Traditional Dairy Products

Abstract: In recent years, exploring novel probiotic strains for therapeutic intervention has been raised due to the significant increase in market demand. This study aimed to investigate the certain probiotic properties of 15 Lactobacillus isolates from Iranian traditional dairy products. Among them, a novel potential probiotic strain was isolated and identified as Lactobacillus crustorum. The characteristics of potential probiotics were examined in terms of resistance to acidity, bile, and salinity as well as antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…The L. crustorum stains have been found in wheat sourdoughs (Scheirlinck et al, 2007;De Vuyst et al, 2009;Ravyts and De Vuyst, 2011), silage (Arasu et al, 2014), the intestine of olive flounder (Kim and Kim, 2013), and milk (Sharafi et al, 2015). To our knowledge, this is the first time they have been found in koumiss.…”
Section: Isolation and Identification Of Bacteriocin-producing Labmentioning
confidence: 65%
“…The L. crustorum stains have been found in wheat sourdoughs (Scheirlinck et al, 2007;De Vuyst et al, 2009;Ravyts and De Vuyst, 2011), silage (Arasu et al, 2014), the intestine of olive flounder (Kim and Kim, 2013), and milk (Sharafi et al, 2015). To our knowledge, this is the first time they have been found in koumiss.…”
Section: Isolation and Identification Of Bacteriocin-producing Labmentioning
confidence: 65%
“…The use of probiotics in enhancing intestinal health has been proposed for several years. The probiotic microorganisms consist of mainly strains from the genera Lactobacillus, Bifidobacterium, Streptococcus, Propionibacteria, Bacillus , and Pediococcus together with some yeasts .…”
Section: Introductionmentioning
confidence: 99%
“…LAB05 showed a decrease in tolerance for most concentrations of NaCl. Studies showed that Lactobacillus strains isolated from traditional Iranian dairy products could tolerate NaCl concentrations up to 5% [26]. Lower concentrations of NaCl (1 to 2.5%) stimulate the growth of Lactic acid bacteria, producing acid which further inhibits the growth of other microorganisms in the GI tract [27].…”
Section: Molecular Identification Of Selected Lactic Acid Bacteriamentioning
confidence: 99%